EFEKTIVITAS SERBUK DAUN PEPAYA (CARICA PAPAYA) SEBAGAI LARVASIDA AEDES AEGYPTI TAHUN 2025 - Soedjadi, Theodorus Teddy Bambang; Mustar Rusli; Sonya Sariara Sipayung (Poltekkes Kemenkes Medan, 2025)
Dengue hemorrhagic fever (DHF) is an infectious disease that remains a public health problem in Indonesia. One control strategy is the use of larvicides. This study aims to determine the effectiveness of papaya leaf powder (Carica papaya) as a larvicide against Aedes aegypti larvae. The study design was a laboratory experiment with variations in concentration of 20 g, 40 g, and 60 g of papaya leaf powder and a control, with 6 replicates. The results showed that larval mortality increased with concentration and exposure time. The 60 g concentration resulted in the highest mortality (55%). The ANOVA test showed p=0.000, indicating a significant difference between treatments. Probit analysis yielded an LC50 value of 3.73% and an LC90 value of 7.55%. Conclusion: papaya leaf powder is effective as a natural larvicide and can be used in dengue vector control.